Crédito e desenvolvimento em economias agroexportadoras: o caso de São Paulo (1850-1930) - Saes, Flávio Azevedo Marques de (Revista do Instituto de Estudos Brasileiros, 1988)
This paper analyses the development of credit and of the banking system in São Paulo from1850 to 1930. It discusses three issues common to literature on the credit of primary exporting economies: the importance of forign banks; the conditions for gaining access to credit in the agricultural sector; and the presence and significance of nationally owned banks. For São Paulo my conclusions point toward the development of a relativelly complex credit system that encompasse: foreign banks dealing with export-import commerce, large foreign enterprises, and foreign exchange; large nationally owned banks primarily connected to commerce and industry as well as a large number of small nationally owned banks (both in the capital and in the interior of the state) that existed precariously; institutions that acted in the agricultural sector, although for the most part these were not very successful. In general, agriculturalists were forced to use indirect means of obtaining credit, especially through personal loans from coffee merchants.